Circulating Microrna-146a as A Biomarker Related To Inflammation in Thalasemia Patients - Heba Hani Hamzah; Nawal Khinteel Jabbar (Academia Open, 2024)
This study delves into the intricate realm of microRNAs (miRNAs), non-coding RNA molecules that wield significant influence in the pathogenesis of various disorders. With the advent of advanced technologies, accurate quantification of miRNA abundance across diverse tissues is now attainable. Notably, extracellular circulating microparticles have emerged as robust, stable indicators for blood-based disease diagnostics. This investigation explores the dynamic interplay between circulating microparticles and clinical phenotypes, offering valuable insights into disease intricacies. The research narrows its focus to recent developments in employing circulating microparticles as biomarkers for prevalent inflammatory disorders, including infections endemic to thalassemia patients in the city of Diwaniyah, Iraq. Current findings paint a promising future for the utilization of circulating microparticles in the management of inflammatory diseases. In conclusion, this comprehensive exploration of miRNA's regulatory role in globin gene expression has the potential to revolutionize the landscape of thalassemia, ameliorating clinical manifestations and symptoms of this debilitating hemoglobinopathy. The identification of miRNAs implicated in the disease's pathophysiology not only paves the way for novel diagnostic markers but also opens new horizons for therapeutic interventions. Highlights : MiRNA Significance: MicroRNAs play a pivotal role in the pathogenesis of various disorders, offering potential insights into disease mechanisms. Circulating Microparticles: Extracellular circulating microparticles are stable blood-based indicators, holding promise for disease diagnostics and management, especially in the context of inflammatory disorders. Thalassemia Insights: This study highlights the potential impact of miRNAs on globin gene expression, offering new avenues for the diagnosis and treatment of thalassemia, a debilitating hemoglobinopathy. Keywords : MicroRNAs (miRNAs), Circulating Microparticles, Thalassemia, Inflammatory Disorders, Disease Diagnostics